PENGARUH ORGANIZATIONAL ATTITUDES DAN ORGANIZATIONAL ETHICS TERHADAP SUSTAINABLE TECHNOLOGY ADOPTION - Donna Mellina Lim; Ibnu Harris (Jurnal Ecoment Global, 2023)
This study aims to determine the effect of organizational attitudes and organizational ethics on the adoption of sustainable technology in MSMEs in Batam City. This study uses a sampling method in the form of Non-Probability Sampling. The sampling technique used in this study was purposive sampling, the sample was taken as many as 150 respondents.The analytical method used in this research is quantitative analysis method and data collection technique by distributing online questionnaires to entrepreneurs and MSME consumers, especially in the culinary field in the city of Batam. This research uses Statistical Product and Service Solutions (SPSS) software version 22.The results show that organizational attitude has a significant effect on the adoption of sustainable technology and organizational ethics has a significant effect on the adoption of sustainable technology.